On Some Lombard Figures in the Church of Volterra during the Fourteenth Century: Giovanni from Milano and Giovannino from Cremona (Studi di storia medioevale e di diplomatica - Nuova Serie, 2020)
The essay aims to highlight the paths that led two Lombards, notary Giovannino from Cremona and vicar Giovanni from Milan, to the 14th century Volterra. Both occupied key positions in the Church of the Tuscan city, one becoming vicar of the bishop-elect Aimerico Cathy, the other becoming a curial notary. The historiographical horizon is that of the mobility of qualified personnel in 14th-century Italy, until now investigated above all for the lay functionary, much less for the ecclesiastical one.
Keywords: Mobility; 14th century; Tuscany; Lombardy; Notaries; Church